Who counts most in sustainable forest management? - Colfer, C.J.P. (1995)
This paper proposes a method for identifying and defining the most significant actors in sustain- able forest management. A rationale for the importance of differentiating among various forest stakeholders is first provided. Significant stakeholders identified in forest management units in Kalimantan, Côte d'Ivoire, and the USA. are described. These descriptions are followed by a discussion of six important dimensions along which groups of people vary in their relations with the forest (proximity, pre-existing rights, dependency, indigenous knowledge, culture/forest integration, and power deficits). Finally, a simple scoring technique is proposed and demonstrated for the three contexts described earlier.